The information diet : a Case for Conscious Consumption - Johnson, Clay A. (Sebastopol, CA O'Reilly, 2012)
"The modern human animal spends upwards of 11 hours out of every 24 in a state of constant consumption. Not eating, but gorging on information ceaselessly spewed from the screens and speakers we hold dear. Just as we have grown morbidly obese on sugar, fat, and flour--so, too, have we become gluttons for texts, instant messages, emails, RSS feeds, downloads, videos, status updates, and tweets. WaldeckWe're all battling a storm of distractions, buffeted with notifications and tempted by tasty tidbits of information. And just as too much junk food can lead to obesity, too much junk information can lead to cluelessness."--Publisher's blurb
Keywords: Tecnología de la información -- Gestión; Libros electrónicos